2016
DOI: 10.2106/jbjs.15.00509
|View full text |Cite
|
Sign up to set email alerts
|

Percent Body Fat Is More Predictive of Function After Total Joint Arthroplasty Than Body Mass Index

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…Obesity is also associated with increased operative time, hospital length of stay, and readmission rates [13], [14]. However, when it comes to patient-reported outcome (PRO) measures, the impact of obesity becomes less clear due to conflicting reports [3], [4], [11], [15], [16] likely reflecting geographic variations, outcome measures used, research methodology, and severity of obesity (all obese patients vs morbidly obese). In addition, most previous studies have focused on TKA, leaving limited information on the effect of obesity on PROs following total hip arthroplasty (THA).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is also associated with increased operative time, hospital length of stay, and readmission rates [13], [14]. However, when it comes to patient-reported outcome (PRO) measures, the impact of obesity becomes less clear due to conflicting reports [3], [4], [11], [15], [16] likely reflecting geographic variations, outcome measures used, research methodology, and severity of obesity (all obese patients vs morbidly obese). In addition, most previous studies have focused on TKA, leaving limited information on the effect of obesity on PROs following total hip arthroplasty (THA).…”
Section: Introductionmentioning
confidence: 99%
“…Although treatment satisfaction outcomes for a particular modality conducted in Western countries should be extrapolated with caution to Japanese patients due to differences in the outcome measurement methods, outcomes after total knee arthroplasty (TKA) were found to be nearly similar across all the studies. 9 11 Predictive factors shown to be associated with TKA satisfaction were higher pre-operative Knee Society Score, 12 low body-fat percentage, 13 and greater pain and disability before surgery. 14 However, no studies have yet been conducted to investigate predictive factors of TSM.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is usually defined by a high BMI, but a diagnosis depending on body‐ or visceral‐fat percentage has been proposed. A study reported the increase in the amount of body fat to be a superior predictor of the occurrence of some medical complications than the increase in BMI (Ledford et al., 2016).…”
Section: Introductionmentioning
confidence: 99%